2010
DOI: 10.1177/104063871002200508
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inoculum Volume on the Microbiologic Detection of Naturally OccurringStaphylococcus AureusIntramammary Infections

Abstract: Abstract. Currently no standard definitions for the diagnosis of Staphylococcus aureus intramammary infection (IMI) exist. As a result, criteria applied in research to diagnose S. aureus IMIs have varied making comparisons between published works difficult. The goal of the current study was to define the optimal inoculum volume used in the diagnosis of naturally occurring S. aureus IMIs. Microbiologic results from 2 field studies examining S. aureus IMIs were used to examine the effects of inoculum volume on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…To summarize, the difference between our obtained estimates (Se, Sp) for PCR and BC and estimates in other studies can be explained by many reasons such as the type of PCR (qualitative or quantitative or semi-quantitative), cut-off choice for Ct value of PCR, IMI definitions on BC (cutoff point for the number of colonies on BC), frequency of sampling (single or duplicate) as reported by Erskine and Eberhart (1988), inoculum volume for BC (Walker et al, 2010), type of samples for BC (premilking sampling or postmilking sampling) as reported by Sears et al (1991), handling of samples (fresh or freezing or centrifugation or non) as reported by (Godden et al, 2002), difference in the time of sampling for BC and PCR, different period of examination (dry off or lactating cows), difference in the sample size and study design, difference in the herds management and milking system (conventional milking systems or automatic milking systems), status of the cow at sampling and their history for S. aureus exposure.…”
Section: Test Estimates Variationscontrasting
confidence: 65%
“…To summarize, the difference between our obtained estimates (Se, Sp) for PCR and BC and estimates in other studies can be explained by many reasons such as the type of PCR (qualitative or quantitative or semi-quantitative), cut-off choice for Ct value of PCR, IMI definitions on BC (cutoff point for the number of colonies on BC), frequency of sampling (single or duplicate) as reported by Erskine and Eberhart (1988), inoculum volume for BC (Walker et al, 2010), type of samples for BC (premilking sampling or postmilking sampling) as reported by Sears et al (1991), handling of samples (fresh or freezing or centrifugation or non) as reported by (Godden et al, 2002), difference in the time of sampling for BC and PCR, different period of examination (dry off or lactating cows), difference in the sample size and study design, difference in the herds management and milking system (conventional milking systems or automatic milking systems), status of the cow at sampling and their history for S. aureus exposure.…”
Section: Test Estimates Variationscontrasting
confidence: 65%
“…16 These results are in agreement with another study, which found a sensitivity of 91% for a 0.01 mL inoculum and 96% for a 0.1 mL inoculum. 17 Sensitivity of PCR methods appears to be very high with higher recovery rates than conventional methods, but caution must be observed with respect to specificity if samples are not collected in a sterile manner due to the fact that the organism is not restricted to the mammary gland. 2,12 …”
Section: Detectionmentioning
confidence: 98%
“…Nevertheless, if a pathogen was recovered only in one pair of the duplicate, the quarter was considered as non-infected according to the microbiological results and was considered to display non--significant growth, except in the case of S. aureus or Streptococcus agalactiae infection. This exception was applied for S. agalactiae because it is regarded as a highly contagious obligate parasite of the bovine mammary gland (Keefe 1997) and for S. aureus due to its peculiar shedding pattern, particularly because the shedding pattern could be below the detection limit of the microbiological method employed (Sears et al 1990, Zecconi et al 1997, Godden et al 2002, Walker et al 2010. (B) Second, the milk sample was regarded as microbiologically positive if at least one of the duplicate samples (single S1 or S2) was microbiologically positive regardless of which mastitis pathogen was isolated.…”
Section: Methodsmentioning
confidence: 99%